Factores que determinan la resiliencia socio-ecológica para la alta montaña andina (2014)
This review article is framed in the development of a doctoral thesis, it analyzes the traditional processes of management and planification which have had a disciplinary approach to cope environmental issues, such as climate change in the high mountain and whose proposal has centered on the management and mitigation of the environmental impacts generated by human activities. However, environmental degradation is increasing, due to the conceptual basis on which are based the management tools are usually decontextualized, assuming that socio ecological relationships can be disaggregated to be analyzed and that natural phenomena are predictable and controllable. Considering this, it is proposed the incorporation of complementary theories such as the socio ecosystems, the resilience, transformability and vulnerability.